Agile extension to the BABOK guide : version 1.0 - International Institute of Business Analysis (Toronto : International Institute of Business Analysis, 2013)
The book provides seven key guidelines for the practice of business analysis within an agile environment. These are supported by discovery framework and a delivery framework that articulate specific techniques proven to be successful for agile teams in delivering value.
Includes bibliographical references and index
usc 25/10/17
Loans
Keywords: Business requirements analysis; Agile software development; Business analysts